2022
DOI: 10.4317/jced.58568
|View full text |Cite
|
Sign up to set email alerts
|

Early permanent dental eruption in obese/overweigh schoolchildren

Abstract: Background The WHO defines obesity as abnormal excessive fat accumulation. Indeed, it is the most relevant nutritional disorder in the developed countries. Nutrition turns out to be relevant for childhood development involving different systems and organs as and including teeth development. Prediction of teeth eruption results of relevance in odontopediatrics and more particularly at transitional stages with mixed dentition. Early teeth eruption can lead to dental defects and eventually to periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…In a recent study carried out on Spanish children, they found that being overweight and obesity increase the probability of early eruption of permanent teeth by 1.5–2 compared to normal-weight children. In addition, as in our study, they found a strong positive relationship between age and the probability of dental eruption, finding that the impact of obesity on dental eruption remains stable for the different age ranges studied [ 42 ]. Arid et al analyzed the percentage of patients with eruptive delay, finding an agreement with previous studies that 100% of underweight children had a significant eruptive delay, compared to 32.5% in overweight children and a 16.67% in obese children [ 11 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In a recent study carried out on Spanish children, they found that being overweight and obesity increase the probability of early eruption of permanent teeth by 1.5–2 compared to normal-weight children. In addition, as in our study, they found a strong positive relationship between age and the probability of dental eruption, finding that the impact of obesity on dental eruption remains stable for the different age ranges studied [ 42 ]. Arid et al analyzed the percentage of patients with eruptive delay, finding an agreement with previous studies that 100% of underweight children had a significant eruptive delay, compared to 32.5% in overweight children and a 16.67% in obese children [ 11 ].…”
Section: Discussionsupporting
confidence: 82%
“…In the analysis of the previous literature on the relationship between BMI and the chronology and eruption sequence of permanent teeth, both longitudinal [ 17 , 36 , 38 ] and cross-sectional [ 2 , 4 , 6 , 20 , 21 , 37 , 39 , 46 , 47 , 48 , 49 ] studies were found. With regard to race, most previous studies were in Asian children [ 4 , 14 , 39 , 47 , 48 ], although there are also some in North American children [ 20 , 35 ], Spanish [ 2 , 42 , 46 ], Central Americans [ 17 ], Africans [ 6 ], Europeans [ 37 ], and South Americans [ 11 , 21 , 49 ]. Regarding the sample size and the age of the children in the existing literature, this is very heterogeneous, ranging between 50 and 3519 participants, and between birth and 19 years of age, with different age ranges between the studies [ 2 , 6 , 17 , 20 , 21 , 35 , 36 , 37 , 42 , 46 , 47 , 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is well known, tooth eruption is a long lasting process (it often lasts years) and there are many factors that can modify this process ( Figure 2 ). One can see how an overweight child or an obese child may have an advanced tooth eruption process [ 3 , 4 , 5 , 8 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Runx and Energy Statementioning
confidence: 99%
“…Some research works conclude that one’s nutritional state can also modify dental eruption timing. It has been shown that children who are obese and overweight can experience early permanent tooth eruption [ 2 , 3 , 4 , 5 ]. In contrast, malnourishment is associated with delayed teething [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%